A comparative study between cemented and un-cemented hemiarthroplasty management of fracture neck of femur in elderly patients - Raj, Rahul; Kumar, Saurabh; Pawar, Shubhadarshini (International Journal of Advances in Medicine, 2022)
Background: Cementation of prosthesis achieves a good initial fix in an osteoporotic bone, however, arthroplasty using a cemented implant may be associated with increased mortality compared with an arthroplasty using an uncemented implant, as it has the risk of bone marrow and fat embolization with resulting intraoperative hypotension and increased incidence of deep vein thrombosis. This aim of the study was to evaluate the complications, morbidity, and mortality rates associated with each of the procedures and study the radiographic changes, recovery to physical independence and advantages encountered in each of the procedures, and achieve stable fixation and early mobilization. Methods: Pre-operative and a postoperative assessment was done on patients who underwent Cemented and Uncemented for femoral neck fractures. After the procedure, the frequent follow-up was carried out. Clinical evaluation was done for limb length discrepancy, thigh pain, rotation of the limb, gait pattern, and range of movements. Results: The incidence of postoperative complications was higher in the uncemented group than in the cemented group. The cemented group showed significantly better results than the uncemented group regarding walking distance. There was a statistically significant difference between the two groups regarding Harris hip score. Conclusions: For elderly patients with a displaced femoral neck fracture a cemented hemiarthroplasty is favorable compared to an uncemented stem. There was no significant overall difference in mortality rate, cardiovascular and cerebrovascular complications, general complications, local complications, and reoperation rate.